The Language of Adolescents in Depicting Migrants. (March 2023) - Albarello, Flavia; Crocetti, Elisabetta; Golfieri, Francesca; Rubini, Monica
This study ( N = 161 Italian adolescents attending 11 th and 12 th grade of secondary school) investigated how adolescents linguistically portray migrants. Over a year and a half, the study considered whether positive factors known to reduce social discrimination – i.e., multiple categorization of migrants and/or respondent's identification with the human group – are associated with relatively unbiased linguistic descriptions of migrants . The coding system included three categories of terms referring to the outgroup: generalized/categorical definitions, individuating piecemeal information or membership in the human group. We found that adolescents who used multiple categorizations to describe migrants and self-identified with the human group (at T1) linguistically described migrants in human and individuating terms (at T2) to a higher extent. The findings are discussed underlying the implications of defining the self and outgroups in multiple complex ways through language, as an ecological means used by adolescents to communicate their views of others.